Prima descrizione in Italia di un caso di adiaspiromicosi polmonare in una lontra eurasiatica (Lutra lutra) - MALATESTA, DANIELA; BONGIOVANNI, LAURA; ROMANUCCI, MARIARITA; PALMIERI, CHIARA; DELLA SALDA, Leonardo; Simpson V; Fusillo R; Marcelli M (2013)
Adiaspiromycosis is a pulmonary disease caused by the inhalation of the ubiquitous fungus Emmonsia spp., a common soil inhabitant. In this disease, the replication and dissemination of the fungus from the primary site are lacking.Members of the Family Mustelidae seem to be highly susceptible to this infection. It has been previously described in otters (Lutra lutra) in Czech Republic/Slovakia, Finland and England. In many cases, Emmonsia-associated lesions have been reported as incidental findings during necropsies of otherwise healthy animals, thus being considered of limited pathological significance. However, fatal adiaspiromycosis has been described in otters as well.As part of the Recal project, a road-killed male Eurasian otter was submitted for the post-mortem examination. Lung samples were fixed in 10% neutral buffered formalin, embedded in paraffin, cut in 5μm-thick sections and stained with hematoxylin-eosin and periodic acid-Schiff (PAS). Histologically, multifocal round structures with a thick trilaminar wall and a central basophilic granular mass were observed within the alveoli. The adiaspores were surrounded by a severe granulomatous reaction with high number of macrophages, multinucleated giant cells, eosinophils, neutrophils and fibroblasts. Numerous multifocal cholesterol granulomas were observed close to those fungal-induced. To the best of our knowledge, this is the first description of adiaspiromycosis in an Eurasian otter in Italy.[.]